Kinerja Kepala Sekolah dan Guru dalam Mengimplementasikan Pendidikan Inklusif - Munawir Yusuf (Jurnal Pendidikan dan Kebudayaan, 2012)
This study aimed to describe the performance of school principals and teachers in implementing inclusive education in primary school. To achieve these objectives, a research survey has been conducted at primary schools that organize inclusive education in 4 area districts, namely Surakarta, Karanganyar, Sukoharjo and Boyolali, in Central Java Province. The numbers of samples in this study were 51 inclusion elementary schools, 51 school principals, and 103 classroom teachers. Data were collected and processed using questionnaires and descriptive statistics, respectively. Questionnaire Validity for School Principals is in the range of 0312-0796 with 0962 reliability. Questionnaire Validity for Teachers is in the range of 0290-0815 with 0956 reliability. The results can be summarized as follows: 1) The performance of school principals in implementing inclusive education is in the medium category; 2) performance of classroom teachers in implementing inclusive education is in the medium category; and 3)Principal performance score average (65.45 %), higher than the average score achieved by teachers (62.3%).